Training Utilization of Artificial Intelligence (AI) to Improve the Competence of Physics Teachers in Facilitating Learning in Langsa City - Saputri, Mawarni; Musdar; Nurulwati; Ngadimin; Hamid, Abdul (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This program aimed to address the limited use of artificial intelligence (AI) in physics education among high school teachers in Langsa City by enhancing their skills in developing AI-assisted learning and evaluation tools. Method: Training was conducted through the MGMP Physics community, involving workshops focused on designing and implementing AI-based educational media and assessments. Practical Application: Teachers gained practical skills to integrate AI into their teaching, enabling more effective and personalized learning experiences for students. Conclusion: The training program was successfully implemented, and its objectives were effectively achieved. Physics teachers in Langsa City showed improved competence in understanding and applying AI in education. The outputs include a service result report, improved teacher skills in developing AI-assisted tools, and an article prepared for publication. Overall, the activity contributed significantly to advancing technological literacy and teaching innovation within the local educational sector.